Morphological Control Over Gel Structures of Mixed Semiconductor‐Metal Nanoparticle Gel Networks with Multivalent Cations. Issue 10 (15th January 2023) - Rosebrock, Marina; Zámbó, Dániel; Rusch, Pascal; Graf, Rebecca T.; Pluta, Denis; Borg, Hadir; Dorfs, Dirk; Bigall, Nadja C.
Abstract: In this work, the influence of two different types of cations on the gel formation and structure of mixed gel networks comprised of semiconductor (namely CdSe/CdS nanorods NR) and Au nanoparticles (NP) as well as on the respective monocomponent gels is investigated. Heteroassemblies built from colloidal building blocks are usually prepared by ligand removal or cross‐linking, thus, both the surface chemistry and the destabilising agent play an essential role in the gelation process. Due to the diversity of the composition, morphology, and optical properties of the nanoparticles, a versatile route to fabricate functional heteroassemblies is of great demand. In the present work, the optics, morphology, and gelation mechanism of pure semiconductor and noble metal as well as their mixed nanoparticle gel networks are revealed. The influence of the gelation agents (bivalent and trivalent cations) on the structure‐property correlation is elucidated by photoluminescence, X‐ray photoelectron spectroscopy, and electron microscopy measurements. The selection of cations drastically influences the nano‐ and microstructure of the prepared gel network structures driven by the affinity of the cations to the ligands and the nanoparticle surface. This gelation technique provides a new platform to control the formation of porous assemblies based on semiconductor and metal nanoparticles. Abstract : Multivalent ions are applied as gelation agents to fabricate mono‐ and multicomponent gel structures. The effect of ion valences on the structure‐property correlation of semiconductor, noble metal, and their heteroparticle gel structures is investigated. The mechanism behind the different gel morphologies (hyperbranched and side‐by‐side arranged building blocks) is revealed by using optical spectroscopy, electron microscopy, and X‐ray photoelectron spectroscopy.